Pengendalian Kualitas Produk Jersey dengan Menggunakan Metode PDCA (Plan Do Check Action) dan FMEA (Failure Mode And Effect Analysis) di DRSPORT.ID - Zulmi Chairul Ikhsani; Nugraha; Dewi Shofi Mulyati (Bandung Conference Series: Industrial Engineering Science, 2024)
Abstract. Drsport.id convection provides sports jersey manufacturing services such as soccer jerseys, futsal, basketball and other sports clothing. Futsal/football jerseys are the products with the highest demand and has set a maximum defect rate of 3% for defects in methods caused by human error factors which result in products not meeting requirements. The aim of this research is to reduce product defects Jersey by using the Plan-Do-Check-Action (PDCA) and Failure Mode & Effect Analysis (FMEA) methods. The Plan stage looks for the most dominant types of defects and looks for the root causes of defective products. The most dominant types of defects for Jersey products were five types. Based on the Pareto diagram, the research focuses on correcting 1 type of defect, namely the type of color defect that does not match the order. The factors causing this defect use a Fishbone diagram. Do stage: determine targets and objectives in corrective action and identify defective products and assisted by the 5W+1H tools. In the Check stage, further inspection was carried out using Failure Mode Effect and Analysis (FMEA), and the highest Risk Priority Number (RPN) 315 for ink leaks or ink not coming out evenly, and the recommended action is form of a checking proposal for machine control. The Action stage carries out repeated checks before the production process, then creates a written standard operating procedure (SOP) in the production section which is easily accessible to workers, improves machine maintenance, especially main machines or old machines with preventive maintenance or periodic maintenance which aims to prevent the machine from being quickly damaged or worn out. Abstrak. Konveksi drsport.id menyediakan jasa pembuatan jersey olahraga seperti jersey sepak bola, futsal, basket dan pakaian olahraga lainnya. Jersey futsal/bola merupakan produk dengan permintaan yang paling tinggi. Konveksi drsport.id telah menetapkan tingkat kecacatan maksimal 3% untuk terjadinya cacat pada metode yang disebabkan oleh faktor human error yang mengakibatkan produk tidak sesuai dengan kebutuhan Konveksi. Tujuan penelitian ini adalah untuk mengurangi produk cacat pada Jersey di Drsport.id dengan menggukan metode Plan-Do-Check-Action (PDCA) dan Failure Mode & Effect Analysis (FMEA). Tahap Plan mencari jenis defect yang paling dominan dan mencari akar penyebab terjadinya produk yang cacat. Jenis defect paling dominan untuk produk Jersey diperoleh sebanyak lima jenis. Berdasarkan diagram pareto, penelitian fokus memperbaiki warna tidak sesuai pesanan, faktor-faktor penyebab defect tersebut menggunakan Fishbone diagram. Tahap Do menentukan sasaran dan tujuan dalam tindakan perbaikan dan identifikasi produk cacat dan dibantu oleh tools 5W+1H. Tahap Check dilakukan pemeriksaan lebih lanjut dengan menggunakan Failure Mode Effect and Analysis (FMEA), dan didapatlah nilai Risk Priority Number (RPN) 315 pada Kebocoran tinta atau tinta tidak keluar secara merata, dan recommended action yang diberikan berupa usulan pengecekan berulang checksheet khusus untuk pengontrolan mesin. Tahap Action melakukan pengecekan berulang sebelum proses produksi kemudian membuat standard operating procedure (SOP) tertulis di bagian produksi yang letaknya mudah dijangkau oleh pekerja, meningkatkan pemeliharaan mesin, khususnya mesin-mesin utama atau mesin yang sudah tua dengan preventive maintenance maupun periodic maintenance yang bertujuan untuk mencegah mesin cepat rusak.